ANALYSIS OF BROCCOLI SUPPLY CHAIN MANAGEMENT Case Study at “X” Fresh Vegetables and Fruits Company, Malang, East Java, Indonesia - Wisynu Ari Gutama; Nadia Gita Damayanti (UPT Penerbitan Universitas Jember, 2012)
The purpose of this research are to know the concept of broccoli supply chain management in “X” Company; analyse the variable value of longterm relationship such as trust, commitment, communication, satisfaction and dependency between “X” Company and broccoli farmers; farmer’s performance level in broccoli supply chain management, and relationship between trust, commitment, communication, satisfaction and dependency and performance level. Methode that used to know the supplier’s performance are Scheduled Orders to Customer Request (SOCR) and Delivery Performance to Request Date (DPRD). Based on the value of the longterm relationship of “X” Company to their suppliers it has a good commitment, often communication, satisfaction and has dependency to them. The performance level, the suppliers has a high on generalizedsituation but in partially, the second supplier is a supplier who has the highest performance level showed by the average value of SOCR dan DPRD for about 77,3 percent which mean that those supplier can fullfiled the “X’s” need for about that percentage. In other hand, based on the variables value of longterm relationship and performance level of suppliers that can be proven that there is a relation between longterm relationship’s variables and the performance level of suppliers.